ANALISIS PROFITABILITAS USAHA KOPI BUBUK PADA INDUSTRI BUMI MUTIARA DI KOTA PALU - Yurhaya Yurhaya; Rustam Abd. Rauf (Universitas Tadulako, 2016)
This study aim was to determine the capital structure, the revenue, and the profitability value ofthe coffee powder Industry of ‘Bumi Mutiara’ in Palu.This research was conducted in the coffe powder industry of ‘Bumi Mutiara’ Earth Industry pearl in Jln. Palu Nagaya 2 No. 29 Palu, Central Sulawesi. Respondents were determined purposively. Primary and secondary data obtained were analyzed using description, revenue and profitabillity analysis. The research results showed that the capital structure of the coffe powder industry consisting of IDR 24 millions for its equity capital, IDR 24 millions for its loan capital obtained from BRI and IDR 50 millions for its mortgage. The total loan capital of the industry was IDR 100 millions with the interest rate of 12% (IDR 500,000/month). The industry had fixed capital of IDR 6.849 millions accumulated in production equipments. The total revenue of the coffee powder industry for a period of three months expanded from December 2015 – February 2016 was IDR 76,852,293. It suggests that the industryis feasible to be developed because it generatesconsiderableprofit. The profitability value of ROI was 36.25% indicating that for each added investment of IDR 100 will resulted in additional profit of IDR 36.25. Whereas, the profitability value of ROE (December 2015 to February 2016) was 288.19% indicating that for each added investment of IDR 100 will resulted in additional profit of IDR 288.19. Keywords: Coffee, Profitability, and Revenue.